2004
DOI: 10.1111/j.1469-7610.2004.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Online aggressor/targets, aggressors, and targets: a comparison of associated youth characteristics

Abstract: Youth aggressor/targets are intense users of the Internet who view themselves as capable web users. Beyond this, however, these youth report significant psychosocial challenge, including depressive symptomatology, problem behavior, and targeting of traditional bullying. Implications for intervention are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

51
721
10
88

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 982 publications
(900 citation statements)
references
References 16 publications
51
721
10
88
Order By: Relevance
“…Previous research has indicated that cyber-aggression perpetration and victimization are related to higher levels of delinquency (Hinduja & Patchin, 2007;Ybarra & Mitchell, 2004a). Studies of traditional bullying also have documented a prospective mean-level relationship between externalizing and bullying perpetration (Sourander et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has indicated that cyber-aggression perpetration and victimization are related to higher levels of delinquency (Hinduja & Patchin, 2007;Ybarra & Mitchell, 2004a). Studies of traditional bullying also have documented a prospective mean-level relationship between externalizing and bullying perpetration (Sourander et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research consistently describes adverse consequences of cyber-aggression, including problem behavior, depressed mood, and lowered self-esteem (e.g. Ybarra et al, 2007;Ybarra & Mitchell, 2004a;Ybarra et al, 2006). However, no research to date has examined how the developmental course of these risks relates to subsequent perpetration and victimization of cyber-aggression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in England, Canada, Australia and USA report a rate of 4%-25% of youth c-victimization and a rate of 11%-17% of c-bullying (Campbell, 2005;Li, 2006;NCH, 2005;Noret & Rivers, 2006;Ybarra & Mitchell, 2004).…”
Section: Bullying and Cyberbullying 8mentioning
confidence: 99%
“…Hostile Attribution Bias and Outcome Expectancies have been found in school Bullying and Cyberbullying 11 11 bullying and aggression between peers, but it has not been examined if the same applies to c-bullying. No research has assessed cognition in c-bullying, nor has any attempted to identify common cognitive factors between t-bullying and c-bullying.Finally, we aimed to see if roles in t-bullying predict the same roles in c-bullying, and test the hypothesis that t-victims engage in c-bullying in order to "take revenge" (Ybarra & Mitchell, 2004). This is also a very new area of research and previous studies have failed to find consistent results due to methodological differences and limitations (Raskauskas & Stoltz, 2007;Ybarra & Mitchell).…”
mentioning
confidence: 98%